EXPLORING THE ETHNOMATHEMATICS OF JAVANESE TRADITIONAL HOUSES - Anggraeni Maha Dewi; Hana Maulida Ramadhani; Fathimah Husna Sarirah; Ahmad Faridh Ricky Fahmy (Ethnomathematics Journal, 2025)
The continuous exploration of the role of mathematics underscores the significance of ethnomathematics research. Ethnomathematics investigates mathematical concepts embedded within diverse cultures. Among the rich array of ethnomathematical objects, Javanese traditional houses stand out as a promising area for investigation. These houses, deeply rooted in a rich cultural heritage, offer substantial potential for understanding and the concrete application of mathematical principles. This study, employing a systematic literature review, aimed to explore the various mathematical concepts inherent in Javanese traditional houses. Data were systematically collected from Google Schoolar (2019-2023), with a specific focus on articles discussing ethnomathematics in traditional houses. The findings reveal the pervasive presence of ethnomathematics within the architecture of Javanese traditional houses, encompassing mathematical concepts such as plane and solid geometry, liners, and geometric transformations (translation, reflection, rotation, dilation) as well as similarity and congruence.